2009
DOI: 10.1007/s00223-008-9214-6
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Cathepsin K Activity in the Young Mouse Causes Hypermineralization of Long Bone and Growth Plates

Abstract: Cathepsin K deficiency in humans causes pycnodysostosis, which is characterized by dwarfism and osteosclerosis. Earlier studies of 10-week-old male cathepsin K-deficient (knockout, KO) mice showed their bones were mechanically more brittle, while histomorphometry showed that both osteoclasts and osteoblasts had impaired activity relative to the wildtype (WT). Here, we report detailed mineral and matrix analyses of the tibia of these animals based on Fourier Transform Infrared (FT-IR) microspectroscopy and imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Despite several studies of this disorder in animal models [Saftig et al, 1998;Gowen et al, 1999;Kiviranta et al, 2005;Li et al, 2006;Boskey et al, 2009], the complete scenario of pycnodysostosis was only recapitulated in the 129Sv inbred strain of cathepsin K À / À mice [Chen et al, 2007]. These authors observed thinner calvarial bones in the mice and speculated that acroosteolysis, spondylolysis, and calvarial thickness could be explained by increased bone resorption due to site-specific variations in cathepsin K action.…”
Section: Introductionmentioning
confidence: 87%
“…Despite several studies of this disorder in animal models [Saftig et al, 1998;Gowen et al, 1999;Kiviranta et al, 2005;Li et al, 2006;Boskey et al, 2009], the complete scenario of pycnodysostosis was only recapitulated in the 129Sv inbred strain of cathepsin K À / À mice [Chen et al, 2007]. These authors observed thinner calvarial bones in the mice and speculated that acroosteolysis, spondylolysis, and calvarial thickness could be explained by increased bone resorption due to site-specific variations in cathepsin K action.…”
Section: Introductionmentioning
confidence: 87%
“…Ϫ/Ϫ mice at embryonic day 18.5 (E18.5) were cleaned of soft tissue, embedded in polymethyl methacrylate, and sectioned at a 2-m thickness prior to examination by Fourier transform infrared (FTIR) imaging spectroscopy as detailed elsewhere (36). Three sections from each bone, including the growth plate, primary spongiosa, and a section of long bone, were analyzed for mineral content, crystallinity, and collagen maturity.…”
Section: Ftir Spectroscopic Imaging Distal Humeri From Wt and Adam17mentioning
confidence: 99%
“…CtsK, which is a cysteine protease that is mainly secreted by osteoclasts, is also produced by chondrocytes and osteoblasts [32,33]. A recent report found that the addition of either a selective inhibitor for CtsK or a broad inhibitor of cathepsin (B/S/L) activity resulted in delayed mineralization in a culture model of mesenchymal stem cells that developed mineral accretion [34]. In addition, Pan et al reported that MIF−/− LDLR−/− mice exhibited suppressed calcification of the aorta compared with LDL−/− mice, possibly due to the reduced elastinolytic and collagenolytic activity of cysteine proteases (e.g., cathepsin S and L) in smooth muscle cells [35].…”
Section: Delayed Bone Turnover and Disordered Mineralization Of Osteomentioning
confidence: 99%